Endogenous phytogormones in leptosporagiate fern Dryopteris filix-mas (L.) Schott ontogenesis - Kosakivska, I.V.; Vasyuk, V.A.; Voytenko, L.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
High-performance liquid chromatography-mass spectrometry (HPLC-MS) identified a complex of phytohormones and determined the character of the accumulation and distribution of gibberellic (GK3), indole-3-acetic (IAA), and abscisic (ABA) acids in the organs of Dryopteris filix-mas at different phases of the sporophyte development. In the period of intensive growth of sporophyte and at the initial stages of spore development, free forms of ABA and GK3 and conjugated IAA dominated in fronds, and conjugated IAA and GK3 and free ABA dominated in the rhizome. At the time of the full maturation of spores, the character of accumulation and distribution of phytohormones changed — in fronds and the rhizome, free IAA and ABA and conjugated GK3 are accumulated. At the end of the vegetation, conjugated IAA and GK3 prevailed in the rhizome and fronds, while the free ABA was localized in fronds, and conjugated ABA in the rhizome. The increase in the amount of free ABA in fronds after the first frosts indicates the participation of the hormone in the formation of protective reactions. The patterns of quantitative and qualitative changes indicate similarities in the functions of key clas ses of phytohormones of fern D. filix-mas and higher flowering plants and the directivity of their physiological effects on the regulation of the processes of differentiation and morphogenesis.